Difference Analysis of Disaster Types and Grading Control Technologies for Risk of Caving of Coal Roadway Roof. (14th April 2021) - Feng, Jicheng; Cheng, Zhiheng; Wang, Hongbing; Shi, Jianjun; Shi, Haoyu; Yin, Shuaifeng
Abstract : In view of the problem of a caving roof along different parts of the same roadway in a mine, this study classifies the mechanical characteristics of the local instability of the roof based on differences in the rock mass media and types of damage. We determine the factors influencing the quantitative relationship between the failure height of the roof and the environment to establish an indicator system for classifying the grades of risk of the roof caving. This is used to predict the height at which the roof caves along the roadway in a coal seam through fuzzy variable weighting analysis. We also develop software for the grading system of risks of caving of the roof and draw a grading map to represent this risk for a roadway in coal seam No. III in Zhaogu Coal Mine No. 2 in Jiaozuo City of Henan Province, China. According to the zoning characteristics of the coal mine, a targeted support design test is carried out in the same intake airway of working face 11030 of the mine. The results show that the proposed classification method conforms to safe practices in underground mining. The stability of the roadway during service and the grades determined using the proposed method were consistent. This has important theoretical significance and practical value for designing support for roadways and timely reinforcements in areas with a high-risk grade to guarantee the safe operation of coal mines.